Analysis and frequency of educational terms in the works of Ljubomir Protić - Parlić Božović, Jasna Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
From the analysis Protic’ s voluminous work we conclude that the author as a representative herbartian’s orientation in Serbian pedagogy views on issues relating to education, emphasized the importance of the defining problem for education in relation to schooling.In  his General education pedagogy term was used in 28 different interpretations. Education occurs in five different forms, namely: "Education will," and (4 times) synonymous with "moral will" (2) "direct the education of moral character" (5), "the education of opinions" (1) "education spirit "(1)" proper education issues "(1). It is notable that unfold in different places of work developed by certain education or broken down in the aforementioned types that make aFrom the analysis of Protić’s voluminous work, we can conclude that the author, as a representative of herbartian’s orientation in Serbian pedagogy, emphasizes the importance of  defining the problem of education in relation to schooling. In his General Pedagogy, the term education was used in 28 different interpretations. It occurs in five different forms, namely: “education will,” (4 times), also synonymous with “moral will” (2); “direct the education of moral character” (5); “the education of opinions” (1); “education spirit” (1); “proper education issues” (1).It is worth noting that these forms unfold separately in his work, but as such they make an incomplete concept. Therefore, they need to be considered synthetically, as a whole, in order for the versatility of his concept of education to be fully appreciated.The paper started with the observation of educational theory (which occurs 2 times) and educational practices (2 times) as well as general questions that carry a multitude of other educational situations and problems. “The task of education” (mentioned 6 times) is synonymous with “educational mission” (6 times) and it is interchangeable with “forms of education” that occurs once only. In terms of factors influencing a personality development, Protić is be said to be of the optimistic orientation and pays great attention to the justification of the educational process, assuring the reader of the “need for education” (three times). He also underlines the “power of education” (three times), but at the same time, excluding the infinity process, the setting of the “boundaries of education” (to be discussed in five attempts).Finally, the inseparability of many issues in Protić’s  “education process” is equal to the unity of “means of education”, “education goals”, “objectives of education”, and “individuality education” in the “educational work”. An educator exhaustively elaborates the “moral” and the “physical” in teaching, while other forms of education are mentioned exclusively using synonyms thus lessening their significance. Protić attempted to denominate certain theoretical, practical and other educational processes: “pedagogical theory” (twice), “educational practice” (twice), “corrective instruction” (twice) with his methods a) “form of educational practice”, and b) the “principle of educational instruction” (one) or “educational work” (five times).Protić justifies the guidelines for the process of education with numerous concepts: “task of education” (six times) synonymous with “educational mission” (five times), “forms of education” (once), “successful education” (once), “need for education” (three times), “the power of education” (three times), “educational success” (once), “substance of education” (once), “standards for education” (once), “the influence of education” (once), “individuality of education” (once) “educational goals” (five times), “the concept of education” (three times), and “education time” (once).Although there are discrepancies in tackling “adult education” among his contemporaries, Protić actively introduces the category of a trainee, which is widely understood and associated to the term “Youth”.According to Protić, “National Youth Education” is divided into two basic types:  “education in the narrow sense” (four times) and “educational practice” (twice). He also differentiates “essentials in education” (once), “education process” (twice), “means of education” (twice) and “educational work” (five times ).Protić illusory tends to define educational success and in order to do so special attention should be paid to “the burden of education”, as well as to point out the “importance of education” and set “standards for education”. In addition, he carefully chooses his synonyms such as “the development and care of the body” for physical education, or “moral commitment” and “moral character” for moral education.n incomplete concept, process or problem that is not encountered on the subject of special synthetic, the total consideration. Protic inspiration in terms of education as a concept had a more complete understanding of the problem in terms of versatility. It started from the observation of educational theory (which occurs 2 times) and educational practices (2 times) as well as general questions that carry a multitude of other "educational situations and problems." "The task of education" (mentioned 6 times) has a synonym called "educational mission" (6 times) that runs parallel to the previous used interchangeably with "forms of education" that only in one place describes. In terms of factors of personality development, for Protića can be said to belong to the optimistic orientation and pays great attention to the justification of educational process, assuring the reader of the "need education" (three times), and including the "power of education" (three times), and at the same time excluding the infinity process, setting "boundaries education" (to be discussed in five attempts). Finally, the inseparability of many issues in Protic's "education process" is equal to unity "means of education", "education goals", "objectives of education" and "individuality education" in the "educational work". Educator exhaustively elaborates mainly "moral" and "physical" in aspitanje, while other forms of education mentioned exclusively using synonyms, putting them in this way, by hand. Protic efforts that certain theoretical, practical and other educational processes bookmark name mainly expressed in the formulation: "pedagogical theory" (twice), "educational practice" (twice), "corrective instruction" (twice) with his methods a "form of educational nastsve" (a), b) the "principle of educational instruction" (one) and "educational work" (five times) Guidelines for the process of education Protic justifies numerous concept. "Task of education" (six times) synonymous with "educational mission" (five times), "forms of education" (one), "successful education" (a) "need education" (three times), "the power of education" (three times), "educational success" (one), "substantially in education" (one), "Standards for Education" (one), the influence of "education" (one), "individuality Education" (once) "educational goals" ( five times), "the concept of education" (three views9 and "time education" (one). Jasnan lack protićevog dealing with "adult education" in relation to his other contemporaries, probably because Protic more actively talking about the category of the trainee, which is widely understood and bounded stage "Youth" ie. youth. So, in the same stage of "National Youth Education," Protic distinguishes two basic "type of education", "Education in the narrow sense") (four times) and "education teaching" (twice). As a methodological performance of "education process" is concerned, Protic different "essential in education" (one), "education process" (twice), "means of education" (twice) and "educational work" (five times ) The ultimate aim of the crown process, Protic illusory tends to "educational success". However, in order to do it arrived in the true sense of the word, should pay special attention to "the burden of education" pravilniomkorišćenju "forms of education" m, to address "important in education" and set "standards for education": Talking about "the impact of education" "individuality education", "educational teaching" in that context speaks of "educational purpose of teaching" and "šprincpu educational classes", he uses carefully selected synonyms synonym for physical education "," the development and care of the body, "a synonym for "moral education" is a "moral commitment" and "moral character", "Education in the narrow sense" (mentioned four times), and stands as a synonym for "immediate moral character education," family education "often replaces cinonimom" good habits in parents' home ", a synonym for school education" is used as a "good habits to her parents' home to continue in school," a synonym for "education will," "education of moral will."
Keywords: frequency of occurrence; analysis; Ljubomir Protić; education